Jasmina Dervišević-Cesić: The river runs salt, runs sweet: A memoir of Višegrad (Reka života teče čas slano, čas slatko - memoari iz Višegrada), Eugen: Panisphere, 1994, str. 208 - Nikolić-Ristanović Vesna Ž. (Temida)
nema